2013
DOI: 10.3329/ijarit.v3i1.16093
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rice Germplasm under Salt Stress at the Seedling Stage through SSR Markers

Abstract: Twenty eight rice germplasms were used for identification of salt tolerant rice genotypes at the seedling stage at the experimental farm and Biotechnology laboratory of the Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh during February 2009 to October 2009. Phenotyping for salinity screening of the rice genotypes was done using salinized (EC level 12 dS m -1 ) nutrient solution in hydroponic system. Genotypes were evaluated for salinity tolerance on 1-9 scale based on seedling growth parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
3
3
0
Order By: Relevance
“…This finding is in agreement with earlier findings that wide genetic variation exists for the traits RL and DWsht in rice under saline conditions at the seedling stage (Maiti et al 2006 ; Al-Amin et al 2013 ; Bimpong et al 2014 ). It has also been reported that salinity stress leads to negative root growth and development (Roy et al 2002 ; Rodrigues et al 2002 ).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with earlier findings that wide genetic variation exists for the traits RL and DWsht in rice under saline conditions at the seedling stage (Maiti et al 2006 ; Al-Amin et al 2013 ; Bimpong et al 2014 ). It has also been reported that salinity stress leads to negative root growth and development (Roy et al 2002 ; Rodrigues et al 2002 ).…”
Section: Discussionsupporting
confidence: 93%
“…For instance some of the tolerant Saltol ILs had plant height reduction below 20% under salt stress compared to as high as 38% among sensitive lines (Table 3). This result agrees with previous research indicating that an increase in salt stress level causes a reduction in plant height of rice [37]. Salt stress could inhibit cell division directly or indirectly, thus resulting in the leaves and stems of the affected plants becoming stunted [42].…”
Section: Effect Of Salt Stress On Agronomic Traitssupporting
confidence: 94%
“…Similar findings about the variability in salt tolerance among rice cultivars at vegetative stage were previously reported [36]. Al Amin et al [37] observed wide variation by using the SES system to classify 28 accessions from various sources. Likewise, a screening of 5000 M4 rice mutant lines from 'IR64' using the SES classification system led to identifying 935 mutant as tolerant; which were further advanced for screening at the reproductive stage.…”
Section: Validation Of Saltol-ils At Vegetative Stagesupporting
confidence: 83%
See 1 more Smart Citation
“…In a range of crops, salinity tolerance at early growth stages often reflects greater tolerance than at later growth stages. For different crops, including tomatoes [ 28 , 29 , 38 ], barley [ 39 ], wheat [ 40 ], maize [ 41 ], cotton [ 42 ], and rice [ 43 ], research has shown that genotypes with enhanced tolerance mechanisms have been selected for their resilience to saline environments at the seedling stage. The aim of our present study was to identify salinity tolerance by phenotyping tomato seedlings using quantitative traits such as reduction in mass of roots and shoots, leaf injury due to salt stress, and tolerance indices derived from dry weights and leaf inorganic ions (K + , Na + , and Ca 2+ ) in order to systematically screen salt-tolerant varieties as well as to understand the biochemical mechanisms of salinity stress tolerance in tomatoes.…”
Section: Discussionmentioning
confidence: 99%